Circular polarised antenna fabricated with low‐cost 3D and inkjet printing equipment. Issue 6 (1st March 2017) - Jun, S.; Sanz‐Izquierdo, B.; Heirons, J.; Mao, C.X.; Gao, S.; Bird, D.; McClelland, A.
Abstract : The fabrication of a patch antenna using low‐cost 3D printing equipment is presented. The circular polarised patch antenna is manufactured by combining inkjet printing and stereolithography technology. The substrate has been fabricated by curing photosensitive resin while the patch element of the antenna has been inkjet printed using silver ink. The printed antenna satisfies the required reflection coefficient, axial ratio and radiation pattern at 1575 MHz. The aim is to demonstrate an inexpensive technology that could be used for the fabrication of antennas on customised 3D printed substrates. The performance of the antenna is summarised through simulations and experimental results.